2011
DOI: 10.3892/ijmm.2011.712
|View full text |Cite
|
Sign up to set email alerts
|

Role of periostin in cancer progression and metastasis: Inhibition of breast cancer progression and metastasis by anti-periostin antibody in a murine model

Abstract: Abstract. Periostin (PN), a secreted adhesion-related protein expressed in the periosteum and periodontal ligaments, acts as a critical regulator of the formation and maintenance of bone and teeth, and also plays an important role in tumorigenesis. Although PN is highly expressed in various types of human cancers, its function is still unclear. In this study, we focused on the exon 17 region of PN, which is alternatively spliced out. To investigate the function of full-length PN with exon 17, we produced a neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
34
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 16 publications
2
34
0
Order By: Relevance
“…Periostin decreases in abundance with involution and levels remain low in mammary involution ECM following postpartum ibuprofen treatment (Table 3). Potentially due to interactions with integrins that promote cell adhesion and spreading, POSTN has been shown to promote tumor growth and metastasis of breast and ovarian tumor cells in vitro [54]. Roles for POSTN in the normal mammary gland as well as with mammary tumor progression remain largely unknown.…”
Section: Resultsmentioning
confidence: 99%
“…Periostin decreases in abundance with involution and levels remain low in mammary involution ECM following postpartum ibuprofen treatment (Table 3). Potentially due to interactions with integrins that promote cell adhesion and spreading, POSTN has been shown to promote tumor growth and metastasis of breast and ovarian tumor cells in vitro [54]. Roles for POSTN in the normal mammary gland as well as with mammary tumor progression remain largely unknown.…”
Section: Resultsmentioning
confidence: 99%
“…POSTN has a characteristic structure ( Figure 1) consisting of four main domains, namely an N-terminus (encoded by exon 1) containing a signal peptide (SP), a cysteine-rich EMI domain (exons 2 and 3) made up of approximately 75 amino acids, and a tandem of four homologous FAS1 domains (exons [3][4][5][6][7][8][9][10][11][12][13][14]. The FAS1 domain is a structural homolog of an insect cell adhesion protein fasciclin I and acts as ligand for cell membrane integrins.…”
Section: Introductionmentioning
confidence: 99%
“…[2] (Figure 1). POSTN isoforms are composed of 751-836 amino acids, and have molecular masses from 83 to 93 kDa [2,11]. The individual isoforms have been identified in various tissues: isoform 1 in human osteosarcomas, isoform 2 in the placenta, isoform 3 in epithelial ovarian carcinoma, and isoforms 2 and 4 in both the normal tissue and cancerous tissue of the urinary bladder [1,2,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…However, previous data have shown that Postn plays a critical role in the establishment of tumor cell niche at secondary sites [22]. Supporting this, administration of Postn neutralizing antibodies in xenograft models of breast and ovarian cancers also suppressed invasion and metastasis [45,46]. …”
Section: Resultsmentioning
confidence: 84%